Cd2+ and Hg2+ affect glucose release and cAMP-dependent transduction pathway in isolated eel hepatocytes - E. FABBRI; F. CASELLI; A. PIANO; G. SARTOR; CAPUZZO, Antonio (Aquatic Toxicology, 2003)
Isolated hepatocytes of the European eel (Anguilla anguilla) have been used as experimental model to characterize the effects of Cd2+ and Hg2+ on either basal or epinephrine-stimulated glucose release. Cd2+ strongly reduced glucose output from cells perifused in BioGel P4 columns and challenged with epinephrine, with a maximum inhibition of 95% reached at 10 μM (IC50 0.04 μM). The epinephrine-stimulated glucose output was also reduced by Hg2+, although a significant inhibition of about 60% was achieved only at 10 μM (IC50 5 μM). The possible influence of Cd2+ and Hg2+ on adenylyl cyclase/cAMP transduction pathway has been investigated, since this system is known to play a pivotal role in the regulation of fish liver glycogen breakdown and consequent glucose release. Micromolar concentrations of both heavy metals significantly reduced the epinephrine-modulated cAMP levels in isolated eel hepatocytes, in good agreement with the reduction of glucose output. Cd2+ and Hg2+ also significantly reduced basal and epinephrine-stimulated adenylyl cyclase activity in liver membrane preparations. A competitive inhibition with respect to Mg2+ was shown by Cd2+ and Hg2+, which significantly reduced the affinity of the allosteric activator for the adenylyl cyclase system. Apparent Km for Mg2+ was 4.35 mM in basal conditions, and increased to 9.1 and 7.1 mM in the presence of 10 μM Cd2+ and Hg2+, respectively. These results indicate that Cd2+ and Hg2+ may impair a crucial intracellular transduction pathway involved in the adrenergic control of glucose metabolism, but also in several other routes of hormonal regulation of liver functions. © 2003 Elsevier Science B.V. All rights reserved.